Cross‐campus collaboration: A scientometric and network case study of publication activity across two campuses of a single institution. Issue 1 (5th December 2012) - Birnholtz, Jeremy; Guha, Shion; Gay, Geri; Yuan, Y. Connie; Heller, Caren
<x xml:space="preserve">Abstract</x> Team science and collaboration have become crucial to addressing key research questions confronting society. Institutions that are spread across multiple geographic locations face additional challenges. To better understand the nature of cross‐campus collaboration within a single institution and the effects of institutional efforts to spark collaboration, we conducted a case study of collaboration at Cornell University using scientometric and network analyses. Results suggest that cross‐campus collaboration is increasingly common, but is accounted for primarily by a relatively small number of departments and individual researchers. Specific researchers involved in many collaborative projects are identified, and their unique characteristics are described. Institutional efforts, such as seed grants and topical retreats, have some effect for researchers who are central in the collaboration network, but were less clearly effective for others.